2008
DOI: 10.1002/pmic.200701148
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic characterization of water buffalo milk fractions describing PTM of major species and the identification of minor components involved in nutrient delivery and defense against pathogens

Abstract: Water buffalo has been studied in relation to the exclusive use of its milk for the manufacture of high-quality dairy products. Buffalo milk presents physicochemical features different from that of other ruminant species, such as a higher content of fatty acids and proteins. We report here a detailed proteomic analysis of buffalo skim milk, whey and milk fat globule membrane fractions. Notwithstanding the poor information available on buffalo genome, identification of protein isoforms corresponding to 72 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 36 publications
4
73
0
Order By: Relevance
“…The relative distribution (in percent) of casein and whey proteins in BM was affected by its somatic cell count (Pasquini et al 2003). Buffalo milk containing high (>1,500,000), medium (±211,000), and low (13,000) somatic cell per milligrams had (Bramanti et al 2003) 30.2 c (Addeo et al 1977) α-s2-casein (α-s2-CN) 5.08±1.56 a 10, 11, 12, 13 -4.84-5.13 24,700 (Felgini et al 2009) 11.9% b (D'Ambrosio et al 2008) 13.0±2.0 c (Bramanti et al 2003) 17.6 c (Addeo et al 1977) α-s1-CN + 44.1 c (Mehanna et al 1982) α-s2-CN 47.8 c (Addeo et al 1977) (Bramanti et al 2003) 14.0 c (Mehanna et al 1982) 15.4 c (Addeo et al 1977) β-Lactoglobulin Table 6 (Pasquini et al 2003). In addition to the quantitative differences in the content of the main protein fractions between buffalo and cow milk, qualitative differences have been found in the amino acid sequence of the main proteins of BM and other ruminants.…”
Section: Major Milk Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative distribution (in percent) of casein and whey proteins in BM was affected by its somatic cell count (Pasquini et al 2003). Buffalo milk containing high (>1,500,000), medium (±211,000), and low (13,000) somatic cell per milligrams had (Bramanti et al 2003) 30.2 c (Addeo et al 1977) α-s2-casein (α-s2-CN) 5.08±1.56 a 10, 11, 12, 13 -4.84-5.13 24,700 (Felgini et al 2009) 11.9% b (D'Ambrosio et al 2008) 13.0±2.0 c (Bramanti et al 2003) 17.6 c (Addeo et al 1977) α-s1-CN + 44.1 c (Mehanna et al 1982) α-s2-CN 47.8 c (Addeo et al 1977) (Bramanti et al 2003) 14.0 c (Mehanna et al 1982) 15.4 c (Addeo et al 1977) β-Lactoglobulin Table 6 (Pasquini et al 2003). In addition to the quantitative differences in the content of the main protein fractions between buffalo and cow milk, qualitative differences have been found in the amino acid sequence of the main proteins of BM and other ruminants.…”
Section: Major Milk Proteinsmentioning
confidence: 99%
“…Based on the amino acid composition, buffalo α s -CN and β-CN were more hydrophobic than their bovine counterpart. Woodward (Yousef et al 1983) calculated the hydrophobicity of buffalo Only 9 substitutions were found between buffalo and cow α s1 -CNs (Table 7) which correspond to 97.2 % homology (Sukla et al 2006;D'Ambrosio et al 2008). However, the buffalo α s1 -CN exhibited lower mobility in alkaline PAGE than its bovine counterpart but with isoelectric focusing, they had similar pI ).…”
Section: Major Milk Proteinsmentioning
confidence: 99%
“…Different approaches, from 2D gels to LC separation, were used to determine the phosphorylation pattern of caseins in human, bovine, equine, goat and buffalo milk (144)(145)(146)(147)(148) . In particular, a study of buffalo skim milk, whey and MFGM reported phosphorylation data on caseins providing scientific basis to coagulation/cheese making processes used in dairy productions (149) . Glycosylation of milk proteins has also been investigated by MS (150,151) .…”
Section: Protein and Peptides As Food Ingredientsmentioning
confidence: 99%
“…The bound proteins were eluted in SDS-PAGE sample buffer, resolved by 12% SDS-PAGE and stained with ammoniacal silver staining 18 . PCLI1 band was excised, in-gel S-alkylated, digested with trypsin, and extracted as previously reported 19 . Digest was solved in 80% v/v acetonitrile, 0.1% v/v trifluoroacetic acid containing 2,5-dihydroxybenzoic acid (20 mg/ml), loaded on a GELoader tip (Eppendorf) packed with TitanSphere TiO 2 resin 5 mm (GL Science Inc.), which was washed and eluted as previously reported 19 .…”
Section: Mass Spectrometric Characterization Of Pcli1mentioning
confidence: 99%
“…PCLI1 band was excised, in-gel S-alkylated, digested with trypsin, and extracted as previously reported 19 . Digest was solved in 80% v/v acetonitrile, 0.1% v/v trifluoroacetic acid containing 2,5-dihydroxybenzoic acid (20 mg/ml), loaded on a GELoader tip (Eppendorf) packed with TitanSphere TiO 2 resin 5 mm (GL Science Inc.), which was washed and eluted as previously reported 19 . Enriched digest was directly analyzed by MALDI-TOF MS and nanoLC-ESI-LIT-MS/MS.…”
Section: Mass Spectrometric Characterization Of Pcli1mentioning
confidence: 99%